Determination of FRET orientation factor between artificial fluorophore and photosynthetic light-harvesting 2 complex (LH2) - Kazuhiro J. Fujimoto; Tomoya Miyashita; Takehisa Dewa; Takeshi Yanai (Scientific Reports, 2022)
Abstract The orientation factor of fluorescence resonance energy transfer (FRET) between photosynthetic light-harvesting 2 complex (LH2) and artificial fluorophore (Alexa Fluor 647: A647) was theoretically investigated. The orientation factor of 2/3, i.e., the isotropic mean, is widely used to predict the donor–acceptor distance from FRET measurements. However, this approximation seems inappropriate because the movement of A647 is possibly restricted by the bifunctional linker binding to LH2. In this study, we performed molecular dynamics (MD) simulations and electronic coupling calculations on the LH2-A647 conjugate to analyze its orientation factor. The MD results showed that A647 keeps a position approximately 26 Å away from the bacteriochlorophyll (BChl) assembly in LH2. The effective orientation factor was extracted from the electronic coupling calculated using the transition charge from electrostatic potential (TrESP) method. With MD snapshots, an averaged orientation factor was predicted to be 1.55, significantly different from the isotropic mean value. The analysis also suggested that the value of the refractive index employed in the previous studies is not suitable for this system. Furthermore, optimal orientations of A647 with larger orientation factors to improve FRET efficiency were searched using Euler angles. The present approach is useful for extending the applicability of FRET analysis.